Sustainable basic education transformation through public-private partnership in Nigeria - Abdullah, Siti Alida John; Abdullahi, Danjuma; Abdulsomad, Kamaruddin (2013)
Private organizations are now the most important actors in provision of quality education in Nigeria government tinance is complemented by inputs from external partners such as NGOs, Communities, household, religious institutions and private companies, though public sector remains an important player in providing education services to the masses but due to economic recession the budgetary allocation to education is fluctuating which is affecting quality education there by denying populace rights to basic education leading to such problems such as prostitution, armed robbery, kidnapping, rise and activities of such groups such as Boko EIaram and Niger Delta militancy, the paper examines roles of public private partnership in providing alternative option as well as challenges of private sector partnership in education finance for the achievement of Education for all in 2015 and attainment of aims and objectives of millennium development goals.The paper relied on content analysis such as text books. journals and reports on the activities of public private partnership.The findings revealed that the relationship between private provision of education and indicator of educational quality is positive, which means that private sector can deliver high quality education at cheaper rate and minimize corruption.The paper suggests increase in public private participation to enhance effective and quality education in Nigeria.